Seasonal variations in the atmospheric concentrations of polychlorinated biphenyls in Kuwait. (December 2017) - Gevao, Bondi; Porcelli, Massimiliano; Rajagopalan, Smitha; Krishnan, Divya; Martinez-Guijarro, Karell; Alshemmari, Hassan; Bahloul, Majed; Zafar, Jamal
Abstract: The spatial and temporal variations in the atmospheric concentrations of PCBs were concomitantly measured at several sites over a twelve-month period in Kuwait to examine seasonal variability and urban-rural concentration gradients using two sampling methods. The annual mean (and range) of ∑PCB concentrations measured using high volume samplers was 10.8 (1.2–32) pg m −3 at the remote site and 39.4 (1.1–128) pg m −3 at the urban site. The median concentrations of ΣPCBs at the urban location (30.3 pg m −3 ) was significantly higher (p < 0.001) than that measured at the remote location (8.6 pg m −3 ) consistent with the view that urban centers are an important net source of these compounds to the environment. Passive sampler derived concentrations across the country showed a uniform distribution except at a few locations in the vicinity of suspected sources where elevated concentrations were measured. As with active sampling data, the concentrations measured using passive samplers were higher in urban areas (range, 4–78 pg/m 3 ) compared to remote sites (range, 2.2–17 pg/m 3 ). The concentrations measured at some urban sites correlated extremely well with mean temperature during the deployment period whereas temperature correlations with measured concentrations were negative at remote and semi-rural sites suggesting that air-surface exchange maybe a key driving mechanism of the current levels of PCBs in Kuwait. Highlights: Study reports on seasonal variability and urban-rural concentration gradients using two sampling methods. PCBs mostly present in the gas phase particularly during hot summer months. The median ΣPCBs concentrations at the urban location significantly higher than at the remote location. Results consistent with the view that urban centers are a net source of PCBs to the environment. Passive sampler derived concentrations showed a uniform distribution except at a few locations.